2014
DOI: 10.1007/s00441-014-2050-2
|View full text |Cite|
|
Sign up to set email alerts
|

The guanine nucleotide exchange factor Vav3 regulates differentiation of progenitor cells in the developing mouse retina

Abstract: The seven main cell types in the mammalian retina arise from multipotent retinal progenitor cells, a process that is tightly regulated by intrinsic and extrinsic signals. However, the molecular mechanisms that control proliferation, differentiation and cell-fate decisions of retinal progenitor cells are not fully understood yet. Here, we report that the guanine nucleotide exchange factor Vav3, a regulator of Rho-GTPases, is involved in retinal development. We demonstrate that Vav3 is expressed in the mouse ret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 83 publications
0
25
0
Order By: Relevance
“…TO-PRO-3 (blue) was used for nuclear counterstaining. The overproduction of different cell lineages has been previously reported (Luft et al, 2015). With ongoing postnatal development, the cellular lineage modification is compensated.…”
Section: Small Gtpases and Vav Genes In Synapse Formationmentioning
confidence: 74%
See 2 more Smart Citations
“…TO-PRO-3 (blue) was used for nuclear counterstaining. The overproduction of different cell lineages has been previously reported (Luft et al, 2015). With ongoing postnatal development, the cellular lineage modification is compensated.…”
Section: Small Gtpases and Vav Genes In Synapse Formationmentioning
confidence: 74%
“…In the light of these observations, we carefully monitored the development of the distinct lineages of the retina in our Vav3 -/-model. We detected an overproduction of Tbr2-positive RGCs, Otx2-positive cone progenitors and an enhanced expression of the late progenitor marker Sox9 in the Vav3 -/-retina, while neither cell death nor proliferation rates were changed (Luft et al, 2015) (Figure 2). These modifications were compensated at later postnatal stages.…”
Section: Vav3 In the Stem Cell Compartment Of The Developing Retinamentioning
confidence: 87%
See 1 more Smart Citation
“…We have previously shown that the treatment of neurospheres with Tenascin C (TnC) led to a decreased expression of Vav3 (Moritz, Lehmann, Faissner, & von Holst, ), and that the cultivation of OPCs on TnC‐coated dishes resulted in impaired OPC differentiation and maturation (Czopka et al, ; Faissner & Reinhard, ; Faissner, Roll, & Theocharidis, ; Garwood et al, ). To investigate whether Vav3 was directly involved in differentiation, we studied OLs obtained from the recently described Vav3 −/− mouse (Luft et al, ). For this purpose, Vav3 +/+ and Vav3 −/− OPCs were isolated via immunopanning and cultivated for 2 days under differentiating conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Here, we investigate the role of Vav3 during OL differentiation and myelination as well as remyelination studying the recently described Vav3 knockout mouse (Luft et al, ). We highlight that Vav3 deficient OLs show an enhanced differentiation, whereas their capacities for myelination and remyelination are impaired.…”
Section: Introductionmentioning
confidence: 99%